Muslim Girl Studies: Bismillahs, Barbies, and Bling (American Journal of Islam and Society, 2008)
A colloquium on “girl studies,” organized by Marcia Hermansen (director,IslamicWorld Studies) and Laura Miller (professor, Department of Anthropology)took place on 12 April 2008, at Loyola University Chicago.Presently, the study of adolescent females – increasingly referred to as girlstudies – as a separate realm of focus is a contested idea in academe.Supporters claim that girl studies is a worthwhile research domain due to theprior disregard for age within women’s studies and gender within youth studies.Detractors note that the category and boundaries of what is considered a “girl” are unstable and historically and culturally varied. More specifically,such scholars as Sharon R. Mazzarella, Norma Odom Pecora, and CatherineDriscoll have argued that over time, literature, popular reading, and consumerismhave become the means through which the mainstream culture instructsgirls on how to become women. In turn, many girls negotiate their interests,sexual expression, body image, and rites of passage in culturally approvedways. Other girls, however, engage in personal, subjective interpretation byrejecting hegemonic standards of femininity in a post-industrial western worldand often in the context of violence, displacement, and resistance.Loyola’s conference highlighted the impact of mainstream norms andethnocentrism in girl studies by including scholarship from a range ofAmerican and non-American cultural contexts. We investigated how girls’lives are constructed in an era of massive change as communities around theworld experience processes of both globalization and localization ...